Caprylic and Polygalacturonic Acid Combinations for Eradication of Microbial Organisms Embedded in Biofilm - Rosenblatt, Joel; Reitzel, Ruth A.; Vargas-Cruz, Nylev; Chaftari, Anne-Marie; Hachem, Ray; Raad, Issam (Frontiers in Microbiology, 2017)
There is a need for non-antibiotic, antimicrobial compositions with low toxicity capable of broad-spectrum eradication of pathogenic biofilms in food preparation and healthcare settings. In this study we demonstrated complete biofilm eradication within 60 minutes with synergistic combinations of caprylic and polygalacturonic acids in an in vitro biofilm eradication model against representative hospital and foodborne infectious pathogen biofilms (methicillin resistant Staphylococcus aureus, multidrug-resistant Pseudomonas aeruginosa, Candida albicans) Escherichia coli and Salmonella enteriditis). Antimicrobial synergy against biofilms was demonstrated by quantifying viable organisms remaining in biofilms exposed to caprylic acid alone, polygalacturonic acid alone or combinations of the two. The combinations also synergistically inhibited growth of planktonic organisms. Toxicity of the combination was assessed in vitro on L929 Fibroblasts incubated with extracts of caprylic and polygalacturonic acid combinations using the Alamar Blue metabolic activity assay and the Trypan Blue exclusion cell viability assay. The extracts did not produce cytotoxic responses relative to untreated control Fibroblasts.